1 - Running While Others Walk: Knowledge and the Challenge of Africa’s Development - Mkandawire, Thandika (Africa Development, 2021)
This article argues that Africa's quest for ‘catch-up’ and economic de- velopment dates as far back, at least, as its humiliating encounter with the West which led to enslavement and colonisation. ‘Development’ is thus not an externally imposed ‘discourse’, but a response to the many challenges the continent has faced over the years and still faces today. Africa lags behind in many social indicators of wellbeing. As a ‘Late, Late Comer’ Africa will, as Nyerere suggested, have to ‘Run While Others Walk’. This demand on the continent to ‘run’ has to contend with a pessimistic discourse that has, against all evidence, insisted that Africans cannot do what many other ‘late comers’ have done or are doing today. The ‘Running’ will demand radical rethinking of institu- tions of collective response to the many challenges about the genera- tion and mastery of the knowledge up to the task, once again placing the universities at the centre of the continent’s development efforts.